2018
DOI: 10.1002/anie.201802946
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Heme Enzyme for Cyclopropanation Reactions

Abstract: An artificial heme enzyme was created through self‐assembly from hemin and the lactococcal multidrug resistance regulator (LmrR). The crystal structure shows the heme bound inside the hydrophobic pore of the protein, where it appears inaccessible for substrates. However, good catalytic activity and moderate enantioselectivity was observed in an abiological cyclopropanation reaction. We propose that the dynamic nature of the structure of the LmrR protein is key to the observed activity. This was supported by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 42 publications
5
97
0
Order By: Relevance
“…In particular, C45/EDA catalyzed cyclopropanation of p-trifluoromethylstyrene and p-methoxystyrene occur with exceptional yield and enantioselectivity for the (R,R) product (99.7% yield & 91.4% ee for F3C-substituted; 90.4% yield & 92.8% ee for MeO-substituted). We postulate that the observed stereoselectivity exhibited by C45 results from the intrinsic asymmetry of the protein scaffold, likely through specific positioning of the reactive carbene adduct as proposed by Villarino et al 24 , and more recently observed in the crystal structure of the methyl-EDA adduct of the engineered cytochrome c 45 . It also offers a means by which we can improve subsequent C45-derived maquettes.…”
Section: Resultssupporting
confidence: 56%
“…In particular, C45/EDA catalyzed cyclopropanation of p-trifluoromethylstyrene and p-methoxystyrene occur with exceptional yield and enantioselectivity for the (R,R) product (99.7% yield & 91.4% ee for F3C-substituted; 90.4% yield & 92.8% ee for MeO-substituted). We postulate that the observed stereoselectivity exhibited by C45 results from the intrinsic asymmetry of the protein scaffold, likely through specific positioning of the reactive carbene adduct as proposed by Villarino et al 24 , and more recently observed in the crystal structure of the methyl-EDA adduct of the engineered cytochrome c 45 . It also offers a means by which we can improve subsequent C45-derived maquettes.…”
Section: Resultssupporting
confidence: 56%
“…This result was achieved by a conservative introduction of only two changes into the sequence of a catalytic amyloid-forming peptide incapable of binding hemin. The efficiencies of these catalysts are comparable to some engineered proteins [11] and demonstrate the ease with which hemin can be employed to promote cyclopropanation in general; however, the observed enantioselectivities are modest, consistent with the lack of a well-defined enclosed catalytic site found in globular proteins. Nonetheless, it is quite striking that self-assembly of short peptides into essentially flat surfaces results in any enantioselectivity at all and this observation suggests the subtle effects of the assembly on the transition state of the reaction.…”
Section: Angewandte Chemiesupporting
confidence: 53%
“…To identify beneficial mutations,e ight residues were targeted (Supporting Information, Figure S2), which are either in close proximity to pAF15 or have previously been identified to improve catalytic parameters of unrelated, LmrR-based designer enzymes. [32][33][34] Libraries targeting each position were constructed using degenerate primers (NNK codons,w hich allow for all 20 canonical amino acids) and approximately 400 library members were evaluated using the previously established screen.…”
Section: Zuschriftenmentioning
confidence: 99%